Chlamydia Trachomatis Infection and Ectopic Pregnancy: Infeksi Chlamydia Trachomatis dan Kehamilan Ektopik - Septian Sima; Nusratuddin Abdullah; Sharvianty Arifuddin; Trika Irinta; Telly Tessy (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To determine the relationship of Chlamydia trachomatis infection in patient with ruptured ectopic pregnancy through examination of endocervical swabs, tubal tissue using Polymerase chain reaction (PCR) and Enzyme linked immunoabsorb and assay (ELISA) serum IgG antibodies Specific to Chlamydia trachomatis.Method: This study was an observational analytic study with a cross sectional study design. In this study, there were 50 participants consisting of 25 ruptured ectopic pregnancy patients and 25 non-ruptured ectopic pregnancy patients who underwent treatment at Dr.Wahidin Sudirohusodo Hospital as well as networking hospitals at the Universitas Hasanuddin in Makassar City.Results: The results showed that Chlamydia trachomatis infection in patients with ruptured ectopic pregnancies was found to be 84% positive in tubal tissue, 72% with endocervical swabs and 64% with serum examination. There was a significant relationship between chlamydial tracheal infection obtained through examination of tubal tissue, endocervical swab and specific serum IgG in patients with ruptured ectopic pregnancy (p <0.001).Conclusion: Based on the results of the study, it can be concluded that Chlamydia trachomatis infection can significantly affect the occurrence of ruptured ectopic pregnancy.Keywords: Chlamydia trachomatis, endocervical swab, ruptured ectopic pregnancy, serum IgG, tubal tissue. Abstrak Tujuan : Untuk mengetahui hubungan infeksi Chlamydia trachomatis pada pasien penderita Kehamilan Ektopik Terganggu (KET) melalui swab endoserviks dan jaringan tuba menggunakan pemeriksaan Polymerase Chain Reaction (PCR) dan Enzyme linked immunoabsorb and assay (ELISA).Metode : Penelitian ini merupakan studi analitik observasional dengan desain studi potong lintang. Pada penelitian ini terdapat 50 orang partisipan yang terdiri atas 25 orang pasien kehamilan ektopik terganggu dan 25 orang pasien non-kehamilan ektopik terganggu yang menjalani pengobatan di RSUP Dr.Wahidin Sudirohusodo serta RS jejaring Universitas Hasanuddin di Kota Makassar.Hasil : Hasil penelitian menunjukkan bahwa infeksi Chlamydia trachomatis pada pasien dengan kehamilan ektopik tergangu didapatkan sebesar 84% positif di jaringan tuba, 72% dengan swab endoserviks dan 64% dengan pemeriksaan serum. Terdapat hubungan yang signifikan antara infeksi klamidia trakomatis yang didapatkan melalui pemeriksaan jaringan tuba, swab endoserviks maupun serum IgG spesifik pasien kehamilan ektopik terganggu (p<0,001).Kesimpulan : Berdasarkan hasil penelitian, dapat disimpulkan bahwa infeksi Chlamydia trachomatis secara signifikan dapat mempengaruhi terjadinya kehamilan ektopik terganggu.Kata kunci : chlamydia trachomatis, jaringan tuba, kehamilan ektopik terganggu, swab endoserviks, serum IgG